Spin diffusion and non-local spin-valve effect in an exfoliated multilayer graphene with a Co electrode. (4th July 2016) - Li, Lijun; Lee, Inyeal; Lim, Dongsuk; Rathi, Servin; Kang, Moonshik; Uemura, Tetsuya; Kim, Gil-Ho
Abstract: We fabricated a non-local spin valve with a thin layer of graphite with Co transparent electrodes. The spin-valve effect and spin precession were observed at room temperature. The magnitude of the mangetoresistance increases when temperature decreases. The spin-relaxation time, τ s, obtained from the fitting of the Hanle curves increases with decreasing temperature with a weak dependence ∼ T − 0.065 while the spin-diffusion constant D decreases. At room temperature, τ s exceeds 100 ps and the spin-diffusion length, λ s, is ∼2 μ m. The temperature dependence of λ s is not monotonic, and it has the largest value at room temperature. Our results show that multilayer graphene is a suitable material for spintronic devices.